Constructing Moduli Spaces of Low Dimensional A[Infinity]-Algebras by Extensions - Frinak, Josh; Ott, Austen (My University, 2012)
Associative or Lie algebras have a product which is a function that takes two inputs and gives one output. Infinity algebras are functions which take any number of inputs and generate an output. This study examines extensions of infinity algebras.
Color poster with text and formulas.
Keywords: Associative algebras; Low dimensional topology; Lie algebras; Mathematical physics; Posters